Polymeric materials for clean water - Das, Rasel (Cham, Switzerland : Springer, 2019)
This book gives an overview of recent developments in the synthesis of macromolecules for water purification applications. The preparation of these polymers from organic and inorganic starting materials is described. Important post-polymerization modifications, introduction of functional groups and production of supramolecular assemblies and nanomaterials are shown. The synthesized materials are presented with their interesting properties and broad areas of applications. A comprehensive discussion about the engineering aspect and the usage in water treatment as well as environmental issues is given. The wide variety of materials and their synthesis techniques will encourage scientists in developing new synthesis routes and materials, whereby engineers will be encouraged to find new possible applications.
Includes bibliographical references.
Keywords: Water -- Purification; Polymers